2015
DOI: 10.1165/rcmb.2014-0232rt
|View full text |Cite
|
Sign up to set email alerts
|

The Roles of MicroRNAs and Protein Components of the MicroRNA Pathway in Lung Development and Diseases

Abstract: Decades of studies have shown evolutionarily conserved molecular networks consisting of transcriptional factors, diffusing growth factors, and signaling pathways that regulate proper lung development. Recently, microRNAs (miRNAs), small, noncoding regulatory RNAs, have been integrated into these networks. Significant advances have been made in characterizing the developmental stage-or cell type-specific miRNAs during lung development by using approaches such as genome-wide profiling and in situ hybridization. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 153 publications
1
27
0
Order By: Relevance
“…Among the discovered miRNAs, some have been found for the first time in this study (ie, miR‐1246 and miR‐1290), while others have already been described and associated with asthmatic pathology . For example, miR‐21 is overexpressed in the asthmatic airways and miR‐146b‐5p is highly expressed in stimulated asthmatic airway smooth muscle cells …”
Section: Discussionmentioning
confidence: 63%
“…Among the discovered miRNAs, some have been found for the first time in this study (ie, miR‐1246 and miR‐1290), while others have already been described and associated with asthmatic pathology . For example, miR‐21 is overexpressed in the asthmatic airways and miR‐146b‐5p is highly expressed in stimulated asthmatic airway smooth muscle cells …”
Section: Discussionmentioning
confidence: 63%
“…Lung cancer is the most common malignancy in humans and is the primary cause of cancer-related mortality in both men and women globally (1,2). Previous studies demonstrated that accumulation of permanent genetic alterations in combination with dynamic epigenetic alterations results in lung cancer formation and progression (3,4). Lung cancer can be divided into two major groups based on pathological features: Small cell lung cancer (SCLC) and non-small cell lung cancer (NSCLC) (5).…”
Section: Introductionmentioning
confidence: 99%
“…Recently it has become apparent that a complex interplay occurs between miRNAs and mRNAs. miRNAs are non-coding RNAs that function as post-transcriptional regulators of gene expression [56]. miR-33 is an upstream regulator of the Wnt signaling pathway and was found to be downregulated in CDH rat fetuses [50].…”
Section: E Rt-qpcr Resultsmentioning
confidence: 99%
“…miR-124 regulates lung epithelial maturation and has been linked to the Wnt/ catenin signaling pathway [53]. miR-142, which is highly expressed in mesenchyme during early lung development, has also been found to interact with the Wnt/ catenin signaling pathway [54][55][56]. The overexpression of miR-375 was found to inhibit alveolar epithelial differentiation by targeting the Wnt/ catenin signaling pathway [57,58].…”
Section: F the Role Of Micrornas In Lung Development Pathwaysmentioning
confidence: 99%